Evaluating the cracking behavior of ECC beam-column connections under cyclic loading by acoustic emission analysis. (10th August 2019) - Abouhussien, Ahmed A.; Hassan, Assem A.A.; Ismail, Mohamed K.; AbdelAleem, Basem H.
Highlights: AE analysis was used to assess the crack growth of ECC beam-column connections under reversed cyclic loading tests. The effect of fibers type on the performance of the specimens was examined. AE b-value and intensity analyses were completed to analyze the AE data. Damage classification chart was developed in terms of intensity analysis parameters. Abstract: This paper presents the results from an experimental program conducted to assess the cracking behavior of reinforced concrete beam-column connections cast with engineered cementitious composites (ECC). Reversed cyclic loading tests in conjunction with acoustic emission (AE) monitoring were completed on all specimens till failure. Four ECC mixtures containing four different types of fibers along with a control conventional concrete (CC) mixture were tested. The AE data obtained from all tests were filtered and analyzed to identify and evaluate the crack growth in all beam-column connections. First, the changes in the AE parameters such as signal amplitudes, number of hits, and cumulative signal strength were considered. Then, additional b-value and intensity analyses on both signal amplitude and strength were performed to develop three further AE parameters including b-value, historic index ( H (t) ), and severity ( Sr ). The impact of fibers type and sensor location on the aforementioned AE parameters was examined. The AE analysis completed in this study led to the identification of the first cracks prior to their visual observation, regardless of fibers type and/or sensor location. The studied AE parameters were highly correlated to the process of crack propagation in all specimens until failure. The results also showed that varying the types of fibers in ECC yielded non-significant effect on the AE signal characteristics (in terms of signal amplitudes) throughout the tests. The intensity analysis parameters ( H (t) and Sr ) were eventually used to generate a damage classification chart to classify the stages of first crack and maximum load in the tested specimens.